Determinants and impacts of financial literacy in Cambodia and Viet Nam - Peter J. Morgan; Long Q. Trinh (Asian Development Bank Institute (ADBI), 2017)
Financial literacy is gaining increasing importance as a policy objective in many countries. However, internationally comparable information on financial literacy is still scarce. The OECD/INFE survey of adult financial literacy is a standardized survey instrument, but so far has mainly been implemented in higher-income countries outside of Asia. Our paper extends the literature by conducting the survey in two relatively low-income Asian economies - Cambodia and Viet Nam - and analyzing the determinants of financial literacy and the effects of financial literacy on other behaviors. Generally our study corroborates the findings of studies of other countries, but uncovers some differences as well. The overall scores of financial literacy in Cambodia (11.5) and Viet Nam (12.0) are at the low end of the range seen in a sample of 30 countries that have implemented the OECD/INFE survey, but they can be considered normal or even high in view of the relatively low levels of per capita income in those two countries. The main determinants of financial literacy are found to be educational level, income, age, and occupational status. Both financial literacy and general education levels are found to be positively and significantly related to savings behavior and financial inclusion, and these results hold even when correcting for possible endogeneity of financial literacy, except for financial literacy in the case of formal savings products in Viet Nam.
Keywords: D14; G11; J26; 330; financial literacy; financial behavior; financial inclusion; household saving; Cambodia; Viet Nam